A Case of IgG and IgA Anti-Laminin-332 Antibody-Positive Mucous Membrane Pemphigoid with IgG and IgA Anti-Envoplakin and Anti-Periplakin Antibodies - Yoshiaki Matsushima; Masako Kitano; Daisuke Hayashi; Hiroyuki Goto; Mako Mine; Takeshi Yokoe; Makoto Kondo; Koji Habe; Yuji Toiyama; Takashi Hashimoto; Daisuke Tsuruta; Kazuhiko Takeuchi; et al. (Dermatopathology, 2022)
A 76-year-old Japanese man presented with a 6-year history of a sore throat. He was treated at several clinics without any improvement before being referred to us. Physical examination revealed widespread erosions and ulcers from the palate to the larynx. Approximately 25 × 15 mm in size, erosive lesions were present on the retroauricular regions, forearms, and glans penis. Pseudomembranous conjunctivitis was also observed. The skin biopsy revealed a partial cleft formation below the epidermis, suggesting subepidermal bullous disease. Immuno-serological tests were negative for anti-desmoglein 1 (Dsg1), anti-Dsg3, anti-BP180, and anti-BP230 antibodies by ELISAs. A whole-body examination revealed gastric cancer. The possibility of mucous membrane pemphigoid (MMP) or paraneoplastic pemphigus (PNP) was considered. Indirect immunofluorescence using rat bladders showed positive IgG reactivity with cell surfaces on the transitional epithelia. Immunoblotting using recombinant proteins of laminin-332 showed both IgG and IgA reactivities with laminin-α3, and immunoblotting using normal human epidermal extract showed double-positive reactivities with envoplakin and periplakin for both IgG and IgA antibodies. Based on the clinical and histopathological features and results of various immuno-serological tests, our case was diagnosed as anti-laminin-332-type MMP with serological findings of PNP. Twenty days after laparoscopic gastrectomy, treatment with oral methylprednisolone 32 mg/day was initiated, and mucosal and skin lesions improved.